If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20-12g=-12g-20+2g
We move all terms to the left:
20-12g-(-12g-20+2g)=0
We add all the numbers together, and all the variables
-12g-(-10g-20)+20=0
We get rid of parentheses
-12g+10g+20+20=0
We add all the numbers together, and all the variables
-2g+40=0
We move all terms containing g to the left, all other terms to the right
-2g=-40
g=-40/-2
g=+20
| 3(x−1)=2(x+3) | | -(b-56)=-4 | | 2x+30=x-23 | | -3(y-95)=66 | | 2(r-18)=-8 | | 1+12/3*7=x | | -4(5+2h)=22 | | g-3/7=3/2 | | 10=3(m+1)+1 | | h+2=10+5h | | 15=3-n | | -b-10=10-5-4b | | 5(d-73)-23=37 | | 9=2(n+3)+1 | | 0=-2(k+1) | | q-10=8+4q | | 2(h+1)+6=16 | | 10h/2=3 | | 17-u=14 | | 760=x²+18x | | 3(t+16)=18 | | 760=x^2+18x | | 6t=5t+4 | | 1/n=-1 | | H=t+4 | | 3(j-9)+1=19 | | 2(d-11)-4=4 | | k(7k+2)=5 | | 14x+64=6x-64 | | 16=12z-100 | | 12x+32=-6x-32 | | x-5=+2 |